Fracture after radiation therapy for femoral metastasis: incidence, timing and clinical features. (15th July 2017) - Shimoyama, Tetsuo; Katagiri, Hirohisa; Harada, Hideyuki; Murata, Hideki; Wasa, Junji; Hosaka, Seiichi; Suzuki, Takayoshi; Takahashi, Mitsuru; Asakura, Hirofumi; Nishimura, Tetsuo; Yamada, Harumoto
ABSTRACT: We analyzed 428 femoral metastases initially treated with radiotherapy between 2002 and 2011 to clarify the clinical details of post-irradiation fractures of femoral metastasis. Patients included 161 men and 167 women, with a mean age of 62 years. Fracture incidence, fracture site, fracture risk based on X-ray images before radiotherapy, and interval from completion of radiotherapy to fracture occurrence were assessed. In addition, 24 pathological specimens obtained during 27 surgeries for these fractures were examined. Fractures occurred in 7.7% of 428 femoral metastases (total 33: 28 actual fractures and five virtual fractures with progressive pain and bone destruction). The fracture rate was 7.8% in the proximal femur and 1.5% in the shaft ( P = 0.001). Fractures occurred a median of 4.4 months after radiotherapy, with 39.4% occurring within 3 months and 63.6% within 6 months. Among femurs with high fracture risk according to Harrington's criteria or Mirels' score, the fracture rate was 13.9% and 11.8%, respectively. Viable tumor cells were detected in all five patients with painful virtual fracture, in 85.7% of femurs with actual fractures that occurred within 3 months, and in only 25.0% of actual fractures occurring after 3 months. Post-irradiation fractures of femoral metastasis most frequently occurred within 3 months after radiotherapy, and were more common in the peritrochanteric area than in the shaft. Radiological evidence of impending fracture did not correlate with a high fracture rate. Actual fractures occurring after more than 3 months were likely caused by post-irradiation fragility of the femur, without viable tumor cells.